Geotechnical properties of Salak Tinggi Residual Soil-Bentonite Mixture as liner / Norazlan Khalid...[et al.] - Khalid, Norazlan; Mukri, Mazidah; Arshad, Mohd Fadzil (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
This paper intends to present an experimental study on the effectiveness of using bentonite mixed with originating sedimentary residual soil as a liner. In order to investigate the effectiveness of soil-bentonite mixture, several tests were performed on Salak Tinggi sedimentary residual soil mixed with different percentage of bentonite content such as 5%, 10% and 15%. The laboratory testing was performed on the mixed sample consist of physical properties of the soil such as: pH, plastic limit (PL), liquid limit (LL), plasticity index (PI), linear shrinkage (LS) and specific gravity (SG). Meanwhile, the compaction testing was performed such as Bristish Standard Light (BSL) and Bristish Standard Heavy (BSH). The compaction test was conducted to determine the maximum dry density (MDD) and optimum moisture content (OMC) at two different compaction energies. The result showed that the addition of bentonite on the Salak Tinggi residual soil can change and improve the physical properties of the results. Moreover, the results of compaction show a decrease in the MDD value for any increase in the percentage of bentonite mixture at all energies. However, MDD value increases with increasing of compaction energy used in soil–bentonite mixture. All these changes improved the performance of residual soil use as liner purposes.